Continuities of Public Service Innovations (PSIs) in Indonesia's Local Governments' Health Services: Whose Initiative Has a Higher Success Rate? - Pratiwi, Pratiwi; Amalia, Shafiera; Wahyuadianto, Agus; Masrully, Masrully; Setya Nugroho, Candra (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2024)
Public Service Innovations (PSIs) have improved public services and increased public values. However, previous studies have shown that public servants saw PSIs as risky interventions because of the perceived uncertain outcomes, lack of support and recognition, opposition against incumbent culture, and negative public scrutiny in case of failure. These perceived risks have led to risk-averse behaviour in public service and incremental or discontinued innovations. Earlier studies on PSIs’ continuity have focused on leadership, engagement, collaborations, and organisational cultures in developed countries. However, the mechanism of engagements, collaborations, organisational culture, and leadership types remains unclear. This study aims to investigate the characteristics of sustainable PSIs in Indonesia and how authorities are exercised. In doing so, 11 PSIs in Indonesian health services—facilitated by staff or leaders—are compared and contrasted. The findings indicate that staff-initiated PSIs are prompted by community needs, use routine visits as a collaboration mechanism, and engage more stakeholders. The shortcoming is that the staff-initiated PSIs need more formal team assignments. The advantage is that they strengthen social capital and decrease community health problems. On the other hand, PSIs that were initiated by formal leaders are stimulated by formal antecedents, such as low achievement of development targets. Leaders-initiated PSIs also use capacity development programs to collaborate and increase the achievement of development targets. A novel finding to add to previous studies is that collaborating with other existing programs contributes to PSIs’ continuity. The managerial implication of this study is to stimulate front-liners in initiating PSIs.